Criminalization of Employers Against Workers in View of The Law - Ibnu Dharma (International Asia Of Law and Money Laundering, 2022)
The relationship between employers and workers is the main thing in business, but this relationship is often a dispute because one party commits non-compliance in implementing the contents of the labor agreement in this case the employer does not pay the normative rights of workers, mutates under pressure / intimidation, Prohibition of organization, discrimination between women workers and male workers and other criminal acts that can harm workers. Policy in handling crime (penal policy) on the creation of harmonization of relations between employers and workers is the concept of labor relations with the industrial family relationship model based on family relationships and togetherness in accordance with the philosophy of industrial Relations. This paper aims to anticipate the criminalization of employer-employee relationships that require norms that regulate equality issues before the law related to labor crimes and supervision and criminal law enforcement, especially in the process of investigating labor crimes handled directly by the police.